Pedro Zulen y el país profundo: correspondencia, descentralismo y praxis filosófica frente a la indiferencia intelectual - Soto Núñez, Luis Daniel (2025)
This article explores the political and philosophical praxis of Pedro S. Zulen through an analysis of his extensive correspondence—over four hundred letters—sent to social actors, delegates, communal authorities, and intellectuals across Peru between 1910 and 1915, during his role as General Secretary of the Pro-Indigenous Association. These letters reveal a political-intellectual network articulated from Lima yet directed toward the realities of the «deep nation,» understood as both historically marginalized and as a site of social agency. The letters document Zulen’s active engagement in concrete causes: denouncing abuses in indigenous communities, providing legal defense for peasants, and coordinating with regional delegates and international anti-slaveryorganizations. The analysis demonstrates that Zulen was not only a critic of centralism and landlordism but developed a situated intellectual praxis, in which philosophy became a mediating force between theoretical reflection and emancipatory action. Contrasted with the prevailing indifference of his contemporary philosophers, often absorbed in abstract debates disconnectedfrom material oppression, Zulen’s legacy emerges as a vital call to reimagine the public role of philosophy and the ethical duty of intellectuals. In a context where territorial inequality and structural racism persist in new forms, his epistolary and political work remains deeply relevant.